Pollen quality and seed yield component responses to pre-anthesis water stress in cultivated and weedy rice (Oryza sativa) - Saragih, Ammini Amrina (2013)
Water stress during reproductive growth stage influences seed yield in cereal crops. The study was aimed to evaluate the differences in the effect of water stress prior to anthesis on plant physiological parameters, pollen and seed yield components of cultivated and weedy rice (Oryza sativa) in order to identify if there is yield and genotypes differences under water stress. Therefore, the suitable genotypes and management practices particularly concerning with water and weed management in the field can be improved to maximize rice production. The study comprised of two seasons of field experiment on two cultivated rice varieties (MR 219, MR 232) and two weedy rice genotypes (collected in Bertam, Penang and Ketara, Terengganu)that were exposed to water stress prior to anthesis for ten days. Physiological parameters like leaf water potential, canopy temperature, photosynthetic rate, stomatal conductance and chlorophyll fluorescence parameters were measured. Pollen qualities evaluated in this study covered pollen number per anther, pollen viability, pollen load on stigma surface and in vivo pollen germination and pollen tube growth, which were observed under fluorescence microscopy. Seed yield components include spikelet number per panicle, spikelet fertility, 100-grains weight and grain yield were determined. Leaf water potential, photosynthetic rate, stomatal conductance and chlorophyll fluorescence parameters reduced significantly in all stressed plants while canopy temperature increased significantly. Pollen number, pollen viability and pollen load of all rice genotypes tested were reduced after experiencing water stress when compared with those in well watered condition. Water stress reduced pollen number by 56-67%. In the first growing season, the reduction in pollen viability was 89-93% in cultivated varieties and 82-85% in weedy rice. In the second season, the reduction in pollen viability was 84-86% and 91-92% for cultivated varieties and weedy rice, respectively. The reduction of pollen load was >80% in both growing seasons for all genotypes. Observation from fluorescence microscopy showed that water stress clearly affects pollen germination and pollen tube growth in both cultivated and weedy rice. Water stress significantly reduced the spikelet number per panicle, spikelet fertility and 100-grains weight of both the cultivated and weedy rice in both growing seasons. The reduction of spikelet number was in the range of 18-21%. Spikelet fertility decreased by 78% for the MR 219, 71% for Bertam weedy rice and 69% for both the MR 232 and Ketara weedy rice. The reduction of 100-grains weight was found to be more sensitive in cultivated rice than the weedy rice. Filled grain or spikelet fertility appears to be the most critical parameter that influenced grain yield in both cultivated and weedy rice if water stress occurs at pre-anthesis. The imposition of water stress for ten days beginning at prior to-anthesis resulting in yields loss in both cultivated and weedy rice. It can be attributed to reduced pollen load and pollen viability which eventually inhibited fertilization. Although both cultivated and weedy rice are critically affected by pre-anthesis water stress, however, cultivated rice appears to be more sensitive than weedy rice in term of greater reduction in seed yield components and grain yield. The findings imply that water stress can promote soil seed bank depletion,therefore, this treatment can be adapted as a method for controlling weedy rice infestation in rice field.